Detection of KRAS mutations of colorectal cancer with peptide-nucleic-acid-mediated real-time PCR clamping. Issue 6 (1st November 2016) - Zhao, Xihong; Chang, Chia-Chen; Chuang, Tsung-Liang; Lin, Chii-Wann
ABSTRACT: Colorectal cancer (CRC) is the third most common cancer in the world and its disease-specific mortality is estimated to be approximately 33% in the developed world. KRAS mutations have been shown to predict response to anti-EGFR (epidermal growth factor receptor) targeted monoclonal antibody therapy. Therefore, KRAS mutation testing of metastatic CRC patients is mandatory in the clinical setting to aid in the choice of appropriate therapy. Currently, the most common strategy for KRAS mutation detection consists of conventional polymerase chain reaction (PCR) and direct sequencing. However, it is a time-consuming and complicated procedure, not suitable for routine clinical test. The objective of this study is to develop and evaluate a highly sensitive and rapid method using peptide nucleic acid (PNA) oligomers mediated real-time PCR clamping for detection of KRAS mutations. The PNA-mediated PCR clamping assay can real-time detect a mutation in a sample containing 1% of the mutant allele in a mixture of wild-type genomic DNA, which also enables the accurate and rapid detection of all KRAS codon 12 and 13 mutations in a single reaction. The total assay time is short as it requires only 1.5 hours after the samples preparation. Thus, the present method offers a potential alternative to be applied in clinical samples of CRC for detection of DNA carrying KRAS mutations.